The Effect of Problem-Based Learning on Students' Problem-Solving and Self-Learning Abilities in Acid-Base - Ivatul Laily Kurniawati (Universitas Negeri Malang, 2022)
This study aimed to determine students' problem-solving and independent learning on acid-base and involved 30 students of class XI MIA SMA Negeri 4 Maluku Tengah. The students were divided into two classes (experimental and control groups), and the chemistry teaching was conducted online because of the Covid-19 pandemic. Data were collected using problem-solving tests and self-learning ability questionnaires. The results showed that the experimental group (problem-based learning class) had better problem-solving and independent learning abilities than the control group (conventional method class). This result implies that problem-based learning improved students' problem-solving abilities and helped them provide appropriate solutions. Problem-based learning also helps students to learn more independently.